2022
DOI: 10.1186/s12916-022-02657-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between gut microbiota and preeclampsia-eclampsia: a two-sample Mendelian randomization study

Abstract: Background Several recent observational studies have reported that gut microbiota composition is associated with preeclampsia. However, the causal effect of gut microbiota on preeclampsia-eclampsia is unknown. Methods A two-sample Mendelian randomization study was performed using the summary statistics of gut microbiota from the largest available genome-wide association study meta-analysis (n=13,266) conducted by the MiBioGen consortium. The summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(193 citation statements)
references
References 71 publications
3
138
0
Order By: Relevance
“…Under this condition, however, the gut microbiota study has almost become the Bi dobacterium's home eld. In contrast, the other study by Pengsheng Li, which used a looser P-value threshold (P < 1 × 10 − 5 ) [15] , will make more sense in the whole gut microbiota eld. Just as Hannah J Jones mentioned in his study, when the instrument sets were small, they included independent SNPs meeting a fatty acid GWAS p-value of 5 × 10 − 5 or less into their instrument sets [16] .…”
Section: Instrumental Variable (Iv)mentioning
confidence: 87%
“…Under this condition, however, the gut microbiota study has almost become the Bi dobacterium's home eld. In contrast, the other study by Pengsheng Li, which used a looser P-value threshold (P < 1 × 10 − 5 ) [15] , will make more sense in the whole gut microbiota eld. Just as Hannah J Jones mentioned in his study, when the instrument sets were small, they included independent SNPs meeting a fatty acid GWAS p-value of 5 × 10 − 5 or less into their instrument sets [16] .…”
Section: Instrumental Variable (Iv)mentioning
confidence: 87%
“…where K represents the amount of IVs, N represents the sample size, total R 2 represents the proportion of variance in the exposure explained by the genetic variants, and by calculating the F-statistic, the strength of IVs was assessed. No significantly weak instrumental bias (Li et al, 2022) was observed when the F-statistic was >10. The inverse-variance weighted (IVW) model was applied as the major statistical method (Chen L. et al, 2022).…”
Section: Statistical Analysismentioning
confidence: 88%
“…Currently, MR studies based on gut microbiome GWAS data are increasingly prevalent. Regarding the selection of IVs for each exposure (taxon), two main parameter settings concerning the threshold of LD r 2 and genetic distance are commonly used: r 2 < 0.001 with 10,000 kb (Li et al, 2022), or r 2 < 0.1 with 500 kb (Ni et al, 2021). In this study, we employed the parameter setting of r 2 < 0.1 with a genetic distance of 500kb to select IVs.…”
Section: Discussionmentioning
confidence: 99%